Mechanical design support in the assembly environment - Kirk, David W. (Cranfield University, 1991)
This thesis proposes a workable application philosophy for state of the art tools operating at the Design/Manufacturing interface. It promotes an organisational approach in developing a framework for a strategic Design For Assembly policy. The definition of Engineering Design is explored. A proposed definition reveals a hierarchial structure. Existing generic design methodologies and specific Design For Assembly techniques are investigated and evaluated against a specific research environment. The research method considers the design/manufacturing interface as a whole. A communication model investigates a mechanism for ratifying design changes. Process control theory explains the control of this mechanism. The research has drawn upon the experience of two collaborators and several case studies are presented. The application domain is complex electro-mechanical products manufactured in a competitive mid volume environment.